Long-Term Follow-Up of Patients With Short QT Syndrome - Giustetto, Carla; Schimpf, Rainer; Mazzanti, Andrea; Scrocco, Chiara; Maury, Philippe; Anttonen, Olli; Probst, Vincent; Blanc, Jean-Jacques; Sbragia, Pascal; Dalmasso, Paola; Borggrefe, Martin; Gaita, Fiorenzo (Journal of the American College of Cardiology, 2011)
The aim of this study was to investigate the clinical characteristics and the long-term course of a large cohort of patients with short QT syndrome (SQTS). SQTS is a rare channelopathy characterized by an increased risk of sudden death. Data on the long-term outcome of SQTS patients are not available. Fifty-three patients from the European Short QT Registry (75% males; median age: 26 years) were followed up for 64 ± 27 months. A familial or personal history of cardiac arrest was present in 89%. Sudden death was the clinical presentation in 32%. The average QTc was 314 ± 23 ms. A mutation in genes related to SQTS was found in 23% of the probands; most of them had a gain of function mutation in HERG (SQTS1). Twenty-four patients received an implantable cardioverter defibrillator, and 12 patients received long-term prophylaxis with hydroquinidine (HQ), which was effective in preventing the induction of ventricular arrhythmias. Patients with a HERG mutation had shorter QTc at baseline and a greater QTc prolongation after treatment with HQ. During follow-up, 2 already symptomatic patients received appropriate implantable cardioverter defibrillator shocks and 1 had syncope. Nonsustained polymorphic ventricular tachycardia was recorded in 3 patients. The event rate was 4.9% per year in the patients without antiarrhythmic therapy. No arrhythmic events occurred in patients receiving HQ. SQTS carries a high risk of sudden death in all age groups. Symptomatic patients have a high risk of recurrent arrhythmic events. HQ is effective in preventing ventricular tachyarrhythmia induction and arrhythmic events during long-term follow-up.